Study the Relationship between FT3, FT4, and TSH with Some Bone Resorption Indexes in Hypothyroidism Men - Asma'a H. Mohamed; Noor S. Naji; Ali H. Al-Saadi (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
The current study was aimed to find the effect of hypothyroidism in men on metabolism and the density of some bone mineral. The study included patients group of 90 men suffering from hypothyroidism and 120 healthy subjects as control group. the study comprised the estimation the concentration of Blood free triiodothyronine (FT3), free thyroid hormone (FT4), thyroid stimulating hormone (TSH), bone resorption index type I collagen C-terminal peptide (CTX-1), the serum calcium (Ca2+), serum phosphorus (Pi3+), the bone mineral density of lumbar spine and femoral neck. The results showed that In the hypothyroidism men group, 1. The bone mass was lower than the control group in significant differences . 2. The level of bone resorption index CTX-1 was significantly higher than that in control group; calcium and phosphorus were not differing from those in healthy control subjects. 3) TSH is positively correlated with CTX-1. male TSH and CTX-1 were positively correlated. Conclusions: There is bone loss in men with hypothyroidism, which may be related to increased bone resorption.